Early-life enrichment in American mink (Neogale vison): Enrichment of the perinatal environment improves maternal nest building and reduces stereotypic behaviour - Gabrielle B Clark; María Díez-León; Rebecca K Meagher (Animal Welfare)
Pens for farmed mink (Neogale vison) commonly include separate nesting areas to provide privacy and warmth in the perinatal period. However, standard bedding materials may not be sufficient to allow intrinsically motivated nest-building behaviours in dams. Further, these materials may not produce optimal nest structures for the rearing of kits. In the present study, we provided extra, relatively high-quality nest-building materials and a chewable sisal rope enrichment for mink dams in the perinatal period (a group enriched at whelping; EW). The effects of these enrichments on various measures of welfare and maternal behaviour were compared to those of mink dams in standard housing (SH) and mink dams whose kits were enriched later in development (EK). EW dams performed less stereotypic behaviour and built higher quality nests than dams of other housing conditions, although dams’ basal faecal cortisol metabolite levels (FCM) were not affected. The stress responsiveness of these dams’ offspring was later assessed by sampling FCM before and after a handling event, however, this event did not appear to induce a measurable stress response and thus no conclusions could be drawn regarding effects of perinatal enrichment on HPA-axis development. Overall, provision of higher quality nest-building materials and a chewable rope enrichment benefited dam stereotypic behaviour and nest building in the perinatal period. We present suggestions for future studies to further investigate whether perinatal enrichment can impact maternal care and offspring HPA-axis development in mink.